Elementary School Students' Character Conditions During Online Learning - Adriana Yuza; Zaka Hadikusuma Ramadan (Jurnal Pendidikan dan Pengajaran, 2021)
Online learning today was said to be unsuccessful and far from expected. It had a less good impact on the formation of characters where children depend heavily on parents and less interaction with others. This was one reason for research aimed at analyzing the implementation of character value in online learning. This type of research is qualitatively discrete. Data was collected from the principal, two teachers who have been certified who have taught for 15 years after the local content teacher. Data collection methods include interviews and observations. The data analysis used was triangulation. The research results stated that implementing the main character values, namely religion, nationalism, media, teamwork, and integrity, is not carried out in the implementation and evaluation stages because learning is done online. So, in online learning, the central values of religion, nationalism, media, teamwork, and integrity are not done, to overcome this can be done by conducting supervision programs.